Why not stop transfer of technology? - Jean-Max Baumer (Intereconomics, 1978)
One of the crucial themes in the dialogue between North and South is the nature and volume of the transfer of technology from the industrialized to the developing world. In contrast to the demand of overcoming the “technology gap“ Prof. Baumer argues that the postulate should rather be formulated as “reduction of technological dependence“.
Keywords: 330; Development